Mind Mapping Method: Its Effectiveness for Teaching Vocabulary - Jamaludin, Habib; Ma'rifatulloh, Sayid (LPPM Universitas Hasyim Asy'ari Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The memorization method used by the teacher made the students bored in their vocabulary class so they had low vocabulary mastery. Therefore, the researchers conducted a pre- experimental study by implementing mind mapping method to teach vocabulary. The study purpose was to find out whether or not mind mapping method was effective for teaching vocabulary. The research design used was one group pre-test post-test. This study population was 180 students of class VIII at a private Junior high school in Gresik. Meanwhile, this study sample was 30 students of class VIII D taken using a purposive sampling. The instruments used were the vocabulary pre-test and post-test. After the pre-test and post-test data was collected, the data were analyzed using descriptive statistics. Then, the data were calculated their normality and analyzed using a paired sample test. The results showed that: (1) the average score of the pre-test was 56.67, the mean score of the post-test was 72 and the sig. (2-tailed) score of the paired sample test was 0.000. Thus, it can be said that the student’s vocabulary mastery became better after the mind mapping method implementation and mind mapping method was effective for teaching vocabulary.